Saving Sophia - Hitchcock, Fleur (Nosy Crow, 2014)
All Lottie wants to do is have adventures, but no such luck. Until she meets Sophia, a girl with an excitingly mysterious history. When the two run away from a staged kayak accident to find Sophia's mum, Lottie learns a lot about having adventures (they're mostly brilliant but not the bits where you nearly die) and friendship and the truth